Spatial Inequality in State of Water Supply and Human Health: A Study of Varanasi City - Pandey, Richa; Singh, Jagadish (National Geographical Journal of India, 2022)
Uncontrolled and unplanned urbanization in cities and towns has caused myriad of problems for livability. Among such problems, inadequacies of piped water supply at home and sanitation form the crux. It would be hard facts to believe that 35 per cent of urban families i.e. 18.7 million households do not get drinking water at home (leaving aside duration and/or quality of water supplied) and for about a third, a house does not include a toilet (2001 census) . In fact, rapid urbanization vis-a-vis unorganized growth of towns and cities in India has put a severe strain on access to infrastructure services like safe water supply, sewerage and drainage, solid waste disposal, etc. If the momentum of economic growth is to be maintained, challenges thrown up by large-scale urbanization will have to be addressed on priority. The urban water supply and sanitation services, particularly in large cities, suffer from shortage of man power, increasing gap between demand and supply, little participation by the users, lack of institutional finance and poor municipal governance. Varanasi - one of the oldest living cities of the world is located along the holy river Ganga but severely faces the problem of inadequate and _ iniquitous distribution of clean water supply across the city which in turn resulted to poor state of health of the people. Keeping the aforesaid fact in background, the present study is designed to examine the inequality in state of water supply and human health in Varanasi - a million+ city of India.